HEALTH PROBLEM ANALYSIS OF CLOSE CONTACT MANAGEMENT OF DIPHTHERIA DISEASE IN MADIUN CITY IN 2023 - Rahman, Airiza; Hendrati, Lucia Yovita; Suroto, Neva Chandra (HEARTY, 2024)
Background: Diphtheria is an infectious disease caused by the bacterium Corynebacterium diphtheriae that can be prevented by immunization. Purpose: The purpose of this research is analyze health problems in the PD3I surveillance program at the Madiun City PP & KB Health Service in 2023. Methods: This research is a descriptive observational research. Prioritize problems using methods of Capability, Accessibility, Readiness, Leverage (CARL). The priority of the problems found is to identify the causes of the problem using fishbone analysis. The root cause of the problem that is found will create alternative solutions to the problem. Results: Management of close contact chemoprophylaxis and re-immunization diphtheria with a CARL score of 400 is a top priority health problem in Madiun City. Four cases of diphtheria have been identified during the year 2023 for a period of six months (January-June 2023), so the next action is to administer chemoprophylaxis to close contacts. The provision of chemoprophylaxis in Madiun City still has problems, namely the activities of drug-taking supervisors who are not health workers and the behavior of dropping out of drug-taking in close contacts due to the side effects of the drug erythromycin. Recommendations: Health workers need to monitor medication supervisors who are not health workers online through WhatsApp groups. Promotion of taking erythromycin medication with meals or after meals to minimize side effects of erythromycin. Promotion of medication adherence in close contacts.